Effects of dehydration performance for cut weight in combat sports - Lopez Gullon, J. M.; Martinez Abellan, A.; de Calasanz Rabadan Iniesta, J.; Casals, C. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
In this review we discuss: I) the physiological and neuromuscular effects described in the literature for different degrees of body mass loss before the official weigh, II) the recovery or "rebound effect" that occurs between the official weigh and the competition beginning, III) the validity of non-invasive markers to estimate hydration status that coaches may use in monitoring the athlete`s weight loss. METHODS: Comparison of various studies in which the hydration status and weight loss of combat sports athletes are analyzed. RESULTS: "Weight loss effects" Dehydration can produce many negative physiological effects that have an obvious repercussion on sport performance, however, it is important the diet applied after weighing up to competition so as not to have a performance loss. "Rebound effect". There are few studies analyzing what occurs in the athletes after the official weighing and the beginning of the competition, it is interesting to know that it occurs in 6 - 18 hours until the beginning of the competition, affecting the athletes` concentration and decision making. "Hydration Indicators". The best method in the majority of investigations is the osmolality in plasma (POSM) or urine (UOSM); although other methods have been reviewed as more economical, such as specific gravity of the urine, urine color, bioelectric impedance, and perception of thirst, being these simpler methods to know the state of hydration. CONCLUSIONS: It is necessary to elaborate a method that allows to know the weight loss habits of the athletes; thus, it could impact on their health and sport performance allowing an optimal recovery for the competition after the weighting. Future investigations are needed to know the rapid weight loss habits and consequences, the level of performance after weighing, and the psychological effects due to the weight loss habits of the athletes.